Development of the Kołobrzeg accommodation base during the first two years of the COVID-19 pandemic - Miedziński, Mariusz (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
The state of COVID-19 as a pandemic, which was announced in Poland from March 20, 2020, significantly influenced the functioning and development of Kołobrzeg, the largest Polish health resort. Despite two lockdowns and restrictions on the functioning of the tourist sector, Kołobrzeg however not only maintained, but even became the largest tourist center in the country. The recorded receipts from the resort for 2021 were 79.47% of the 2019 figure and this combined with having 6.6% of all beds per person per night in July and August 2021 in the whole of Poland, prove the exceptional concentration and strength of this tourist area. The very favorable natural and geographical conditions of the Kołobrzeg health resort, combined with constantly improving transport accessibility, has resulted in further expansion of the accommodation base of the Kołobrzeg urban area, despite the threats from the COVID-19 pandemic. In the studied area, in 2020/2021, a total of 94 investments were implemented, including 14,065 rooms, mainly in hotels, aparthotels, apartment and residential buildings with a total area of approx 748,400 m2, allowing for a further 45,000 people to stay there. The scale and variety of investments in Kołobrzeg have put it at the forefront of the fastest growing resorts despite the COVID-19 pandemic. The city of Kołobrzeg and six neighboring coastal towns will have an accommodation base with a total of over 200,000 beds by around 2024, becoming probably the largest concentration of tourist accommodation facilities on the Baltic Sea.